TOTAL ASAM, TOTAL YEAST, DAN PROFIL PROTEIN KEFIR SUSU KAMBING DENGAN PENAMBAHAN JENIS DAN KONSENTRASI GULA YANG BERBEDA - Amanda Liana Aristya; Anang M. Legowo; Ahmad N. Al-Baarri (Universitas Muhammadiyah Semarang, 2013)
Research goat milk kefir with the addition of the type and concentration of sugar in different level have been conducted in order to analyze the effect and interaction of the two treatments on total acid, total yeast and protein profile of goat milk kefir. The experimental design was used the completely randomized design (CRD) factorial pattern consisting of 2 (two) factors, the first factor (A) is a type of sugar consists of 3 (three) types of treatment (white sugar, brown sugar and D-Psicose) and The second factor (B) is the concentration of sugar consists of 3 (three) standard treatment (4%, 6%, and 8%), each treatment performed repetitions for 3 (three) times. Data results of total acid and total yeast were analyzed using analysis of variance to determine the effect and treatment interaction, while data from the protein profiles was used descriptive analysis. If there is a significant effect of treatment, therefore, continued by Duncan's test Dual region to determine differences among treatments. The results showed that the treatment of sugar (granulated sugar, brown sugar, and D-Psicose), concentration (4%, 6%, and 8%) and the interaction between the two treatments has the affect significantly (p <0.05) to total acid and total goat milk kefir yeast. Types of proteins and the molecular weight of goat milk kefir with the addition of different types and concentrations of the lactoferrin (80kDa), Laktoferoksidase (70kDa), α-Casein (65kDa), and β-casein (45kDa).